International humanitarian aid to North Korea: Progress, results, and controversy - Hazel Smith; Suk Lee (Korea Development Institute (KDI), 2023)
Since the first provision of international food assistance in the mid-1990s, humanitarian aid to North Korea has been a constant source of scrutiny and debate. It was not only a major contributing factor to ending the devastating famine in the mid-to-late 1990s, but it has continuously helped with improving both the food situation and public welfare. Above all, humanitarian aid has become a vital channel that connects North Korea with the global community, and the increased contact that providing humanitarian aid has enabled has led many to believe that cooperating with the once hostile and isolated society may not be entirely impossible. Despite the advantages, however, there has been never-ending controversy surrounding the humanitarian aid to North Korea aid. Some of the main issues include whether the aid is being misappropriated to those in power and the military, whether the aid has had an actual impact on vulnerable groups, why the regime accepts help but continues to provoke, and whether, under the circumstances, humanitarian aid even needs to continue. Of course, we do not have a definite answer to any of these questions as of yet. But, it has been over 20 years since North Korea received humanitarian aid and it has yielded vast amounts of information and data. Accordingly, we would like to examine this from diverse aspects with one of the world's leading scholars in the field, Professor Hazel Smith.
Keywords: 330